Предмет: Алгебра,
автор: AnteK
(x-1)(x^2-3)+(2x-1)(x^2+2)=3
Ответы
Автор ответа:
0
x^3-x^2-3x+3+2x^3+4x-x^2-2=3
3x^3-2x^2+x-2=0
(x-1)(3x^2+x+2)=0
D=1-2*3*4<0 => корней нет
ответ: х=1
3x^3-2x^2+x-2=0
(x-1)(3x^2+x+2)=0
D=1-2*3*4<0 => корней нет
ответ: х=1
Автор ответа:
0
По какому принципу ты вынесла за скобки?
Похожие вопросы
Предмет: Физика,
автор: carolldenver
Предмет: Русский язык,
автор: Ishbghhb
Предмет: Другие предметы,
автор: albertersov
Предмет: География,
автор: kamyshievairinа
Предмет: Литература,
автор: dashakohno